A cross-sectional analysis of intestinal parasitic infections among the general population in north of Iran: Intestinal parasitic infections in north of Iran - Pagheh, Abdol Sattar; Sharif, Mahdi; Daryani, Ahmad; Yazdani-Charati, Jamshid; Nazar, Eisa; Asfaram, Shabnam; Hosseini, Seyed-Abdollah; Tork, Mostafa; Soosaraie, Masoud; Syadatpanah, Abolghasem; Gholami, Shirzad; Mirshafiee, Siavash; et al. (The Journal of Infection in Developing Countries, 2018)
Introduction: Intestinal parasitic infection (IPIs) is one of the most important health problems in the developing countries. Study on the prevalence of IPIs in various communities is a prerequisite for the development of appropriate control strategies. The aim of this study was to evaluate the prevalence of intestinal parasites among the general population in Mazandaran province, northern Iran. Methodology: This study was conducted on 4,788 specimens collected from 17 urban areas (2,515 samples) and 34 rural areas (2,273 samples) within January-December 2016. Fecal specimens were examined by direct wet mounting, formalin-ether concentration, modified Ziehl–Neelsen, and trichrome staining methods. Results: The overall infection rate of intestinal parasite was 14.2% (680/ 4,788). Blastocystis hominis and Giardia lamblia were identified as the most frequent parasites. Protozoa, helminths, and polyparasitism (co-infections with two or more parasite species) were observed in 12.3%, 1.03%, and 0.85% of the specimens, respectively. Furthermore, IPIs showed a significant association with household income, place of residence, washing of vegetables, exposure to soil and season (p < 0.05). Conclusions: Based on the findings, parasitic infections are still a major public health concern in the north of Iran that requires special attention. Therefore, the major key to success in the prevention of IPIs is the execution of some interventions, including patient screening and treatment, public education, and improvement of sanitary conditions.